Determination of liability based on evidence provided by a polygraph testing expert opinion - Krasoń, Robert (Acta Universitatis Lodziensis. Folia Iuridica, 2015)
The study “Determination of liability based on evidence provided by a polygraph testing expert opinion” addresses a very serious and at the same time controversial problem of evidence (its value) provided by a polygraph testing expert opinion. The author familiarizes the reader with a general background of the issue, presenting a concept and importance of liability as well as the essence and nature of polygraph testing. The text contains a number of arguments both supporting and discrediting the diagnostic value of the polygraph testing and a number of doubts arising in connection with this subject.